Alternative approaches to evaluation in empirical microeconomics - Richard W. Blundell; Monica Costa Dias (Centre for Microdata Methods and Practice (cemmap), 2002)
Four alternative but related approaches to empirical evaluation of policy interventions are studied: social experiments, natural experiments, matching methods, and instrumental variables. In each case the necessary assumptions and the data requirements are considered for estimation of a number of key parameters of interest. These key parameters include the average treatment effect, the treatment of the treated and the local average treatment effect. Some issues of implementation and interpretation are discussed drawing on the labour market programme evaluation literature.
Keywords: J21; J64; C33; 330; Evaluation methods; matching; instrumental variables; social experiments; natural experiments; Mikroökonometrie; Test; Wirtschaftspolitik; Wirkungsanalyse; Bewertung; Theorie